Application of Direct Instruction Learning on Ribbon Embroidery Material in SMKN 3 Kediri - Siti Muthiatus Sholichah; Peppy Mayasari; Deny Arifiana; Lutfiyah Hidayati (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The purpose of this study is to describe the learning outcomes of students with the application of Direct Instruction learning in making ribbon embroidery in class XI Clothing 2 SMKN 3 Kediri. This study is a descriptive quantitative study using a one-shot case study research design. This study was located at SMKN 3 Kediri City in the even semester of the 2023/2024 academic year. The population and sample used purposive sampling techniques totaling 30 students of class XI clothing 2. The research instrument used a learning outcome assessment rubric that had been set in the school curriculum. The data collection technique used ribbon embroidery outcome assessment. The data analysis technique used descriptive analysis. The results of the study showed that the learning outcomes of students applied to Direct Instruction learning had satisfactory results, as evidenced by the data on student learning outcomes in making ribbon embroidery with the application of Direct Instruction getting 100% of students completing the results from 30 students in class learning, which can be categorized into very good criteria.